Physical Properties of Turpentine and Gum Rosin Pinus merkusii Jungh et de Vriese Tapped Oleoresin by Borehole Method - Sukarno, Agus (Graduate School, Universitas Brawijaya, 2018)
This study was conducted to determine the physical properties of turpentine and gum rosin derived from oleoresin tapped with borehole method. The research material is derived oleoresin from Aceh provenance pine and Jember landrace. The test results of the physical properties of turpentine are as follows; color: clear, specific gravity 0.84-0.85, refraction index 1.46, negative fatty oil, flash point 34-35.5°C, residual evaporation 1.2-1.6%, and optical round + 32.2-32.4o. Result of test of physical properties of gum rosin: color X (main), softening point 76.0-76.5°C, impurity 0.0014-0.0051%, acid value 179.5-188.5, saponification value 188.7-194.3, iodine number 9.6-9.8, ash content 0.001-0.005% and volatile turpentine content 2.1-2.4%. Keywords: Aceh provenance pine, borehole method, gum rosin, turpentine.